2′-Fucosyllactose Increases the Abundance of Blautia in the Presence of Extracellular Fucosidase-Possessing Bacteria - Horigome, Ayako; Hashikura, Nanami; Yoshida, Keisuke; Xiao, Jin-zhong; Odamaki, Toshitaka (Frontiers in Microbiology, 2022)
Blautia is a genus of anaerobic bacteria that is widely distributed in the mammalian gut. Recently, an increasing body of research has demonstrated a link between this genus and human health, suggesting applications as a novel probiotic strain. Moreover, we have previously shown that 2′-fucosyllactose (2′-FL), a major component of human milk oligosaccharides, increases the relative abundance of Blautia sp., particularly Blautia wexlerae, in the cultured fecal microbiota of healthy adults using a pH-controlled single-batch fermenter. However, the effects of 2′-FL on Blautia proliferation vary among individuals. In this study, we assessed the impact of the intrinsic gut microbiota on the prebiotic effects of 2′-FL. Metagenomic analysis of feces collected from all donors showed that the homolog of the intracellular GH95 α-l-fucosidase gene was considerably enriched in two non-responders (individuals who showed no increase in Blautia proliferation), whereas the homologous genes encoding extracellular α-l-fucosidase were more abundant in responders, suggesting that lactose and fucose released into the environment could be substrates mediating the growth of Blautia. In vitro assays confirmed the ability of B. wexlerae to utilize the two carbohydrates but not 2′-FL. We also observed that B. wexlerae utilized fucose released from 2′-FL by Bifidobacterium bifidum, which possessed extracellular GH95 α-l-fucosidase, in co-cultures of these two organisms. Finally, increasing the proportion of extracellular GH95 by the addition of a B. bifidum strain led to Blautia proliferation by 2′-FL in fecal cultures of the two non-responders. These findings provided valuable perspectives on individualized nutritional approaches to properly control the gut microbiota. Future clinical trials are needed to obtain further insights into the characteristics of responders vs. non-responders.